Halophilic bacteria with potential for the recovery of salinated soils in Sáchica-Boyacá, Colombia - Rodriguez Aristizabal, Monica Alejandra (2019)
It is possible to use halophilic bacteria isolated from saline environments as a possible alternative for the rehabilitation of salinated soils for agricultural and agricultural production. Six halophilic bacteria were evaluated to determine their potential in the reduction of the electrical conductivity (Ce) of moderately saline soil in the municipality of Sáchica-Boyacá (Colombia). The bacteria were isolated on nutritive agar with different concentrations of NaCl, then inoculated in the soil (3 kg placed in pots) to perform a bioassay in the greenhouse for 2 months. Two phases were carried out, the first until obtaining a value of 2 ds / m (Ce) in order to plant tomato plants in the second phase. Weekly measurements of the (Ce) were made throughout the bioassay and only in phase 2 were determined weekly qualitative variables of tomato growth (height, number of leaves, foliar area, wilting and chlorosis). The results showed a direct effect of the halophilic bacteria in the decrease of the (Ce) of the soil, going from 5.2 to 0.8 ds / m (T1), 0.7 ds / m (T2), 0.8 ds / m (T3), 0.6 ds / m (T4), 0.7 ds / m (T5), 0.7 ds / m (T6), 3.0 ds / m (Control), values that correspond to very light salinity (< 2 ds / m). Regarding the agronomic variables, improvements were observed in the characteristics evaluated in comparison with the absolute control, especially in height and number of leaves of the plants. For the absolute control 80 % of the experimental units were lost, while in the soil with the different treatments only in some cases 20 % was lost. Accordingly, it is evident that the halophilic bacteria used in this research have potential for the rehabilitation of salinated soils.